Immune Responses to SARS-CoV, MERS-CoV and SARS-CoV-2 - AKKOÇ, TUNÇ (My University, 2020)
The world has given an outbreak alarm in the last two decades, with different members of the coronavirus family infecting people at different times. The spread of the SARS-CoV-2 virus, which last appeared in December 2019 in China and spread rapidly to all over the world, has led the scientific world to studies on these viruses. While scientists are trying to develop vaccines or drugs against the virus, the body's immune response to the virus is emerged the biggest guide. In this review, we aimed to provide a good view on immune strategies by comparing immunological responses to SARS-CoV-2 disease among other members of the family, SARS-CoV and MERS-CoV. In the near future, it may contribute to vaccine or drug studies to be developed on immune intervention.
Keywords: Humans; COVID-19; SARS-CoV-2; Betacoronavirus; Coronavirus Infections; Pandemics; Pneumonia, Viral; Corona virus; Covid-19; Immune response; Mers-CoV; Middle East Respiratory Syndrome Coronavirus; SARS Virus; Sars-CoV; Severe Acute Respiratory Syndrome